Optimization of simultaneous voltammetric determination of pyridoxine and caffeine - Nawar, Amir Shaaban Farag Moham; Sýs, Milan; Vytřas, Karel (BEST Servis, 2018)
This electrochemical study is focused on finding the optimal working conditions necessary for simultaneous voltammetric determination of xanthine alkaloid caffeine and pyridoxine (vitamin B6) dietary food supplement. Consequently, the aim is to develop a simple method which should be suitable for monitoring of these biologically active organic compounds in commercial energy drinks. This contribution should be understood as an initial study of the simultaneous determination of both substances. Their anodic oxidation at a glassy carbon electrode coated with a thin layer of Nafion® using differential pulse voltammetry in the Britton-Robinson pH 4.5 buffer as the supporting electrolyte has been optimal for the time being. Further, the addition of small amounts of selected surfactants (nonionic Triton X-100, anionic sodium dodecyl sulfate, cationic cetylpyridinium chloride, and 1,3-didecyl-2-methylimidazolium chloride) to the selected BRB solution was tested to improve the repeatability of the obtained results.
Optimalizace simultánního voltametrického stanovení pyridoxinu a kofeinu
Keywords: Carbon nanomaterials; caffeine; energy drinks; glassy carbon electrode; Nafion®; pyridoxine; surfactant; Uhlíkové nanomateriály; kofein; energetické nápoje; elektroda ze skelného uhlíku; Nafion®; pyridoxin; povrchově aktivní látka